2022
DOI: 10.1108/scm-05-2021-0220
|View full text |Cite
|
Sign up to set email alerts
|

Managing triadic supplier relationships in collaborative innovation projects: a relational view perspective

Abstract: Purpose Suppliers are essential partners in innovation projects, as they own resources, knowledge assets and capabilities that complement those of buying firms. In today’s competitive environment, firms may choose to collaborate with suppliers beyond dyads, forming triadic or three-party relationships. Using the theoretical lens of the relational view (RV), this study aims to explore what type of triad configurations firms use to govern supplier relationships in collaborative innovation projects, how they choo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 67 publications
(126 reference statements)
0
37
0
Order By: Relevance
“…However, in this study, we have revealed that ethical perceptions of the buying firm in the mind of suppliers would positively influence the propensity for collaboration, particularly during the supply crisis. The findings explain why suppliers prefer to share resources with selected buying firms and not with all of them ( Pulles et al, 2016 , Moradlou et al, 2022 , Patrucco et al, 2022 ). Prior literature also indicates that opportunism and transaction-based B2B buyer-supplier dealings will actually fail to work under COVID-19.…”
Section: Discussionmentioning
confidence: 91%
“…However, in this study, we have revealed that ethical perceptions of the buying firm in the mind of suppliers would positively influence the propensity for collaboration, particularly during the supply crisis. The findings explain why suppliers prefer to share resources with selected buying firms and not with all of them ( Pulles et al, 2016 , Moradlou et al, 2022 , Patrucco et al, 2022 ). Prior literature also indicates that opportunism and transaction-based B2B buyer-supplier dealings will actually fail to work under COVID-19.…”
Section: Discussionmentioning
confidence: 91%
“…Thus, the learning by interaction (Patrucco et al , 2022) enhances the breadth and depth of the learning process of suppliers and source of implementation of new aspects in formal and informal routines, has a positive effect on the cumulative learning stock of the suppliers (Corradini and D'Ippolito, 2022). The respondents narrated as:…”
Section: Resultsmentioning
confidence: 99%
“…Given that major buyers tend to require high fashioned and sophisticated products, processes and treatments, suppliers need to modernize their operations and production facilities to match the buyers’ specifications (Grönroos and Voima, 2013). In addition, the suppliers modernize their production capabilities to create the needed value for the buyers and themselves (Anning-Dorson et al , 2018; Patrucco et al , 2022) over time.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent decades, innovation has become an inevitable part of supply networks, and studies show that it is increasingly collaborative in nature (Baldwin and Von Hippel, 2011; Chapman and Corso, 2005; Patrucco et al , 2022). For example, supplier collaboration, customer involvement in product development and innovation in networks involving multiple actors are high on the agenda for industry and academia.…”
Section: Introductionmentioning
confidence: 99%